Management of ankyloglossia (tongue tie)-A Case Series - Ashwini Koti; Rathnashree .; Sadiya Naz; Bharath Vardhana; Priya Subramaniam (RGUHS Journal of Dental Sciences)
Ankyloglossia commonly referred to as tongue-tie is a condition caused by a short and thick lingual frenulum leading to restricted tongue movement. This limitation can result in functional complications such as abnormal speech malocclusion midline diastema mandibular lingual gingival recession and difficulty swallowing. These challenges can significantly impact an individuals daily activities and quality of life. In this report treatment was followed by post-operative recall and speech therapy sessions resulting in marked improvement in tongue mobility and speech across all treated cases. Diagnosis was conducted clinically using Kotlowrsquos classification. The findings highlight that the conventional scalpel-based method of frenectomy is relatively painless reliable and effective. Unlike some newer methods this technique consistently ensures successful outcomes reaffirming its value in the management of ankyloglossia.